Upaya Meningkatkan Kreativitas Membentuk Balok Bangunan Melalui Metode Praktik Langsung pada Anak Kelompok A TK Negeri Kabupaten Temanggung - Rukiyati Rukiyati (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2020)
Block play is the ability in constructive activities by building complex buildings using unit blocks that can improve the ability of eye and hand coordination, train fine motor skills, train children in problem solving, games that give children freedom of imagination, so that new things can created as a child's creativity a creative idea. The rationale for this improvement in learning is the lack of creativity in children. The purpose of this study are: 1) to know that through the direct practice method can increase creativity in forming building blocks in children, 2) to find out the magnitude of the increase in creativity in forming building blocks through direct practice methods in children Group A Kindergarten State Temanggung Regency Semester I 2016/2017 Academic Year. The subjects of this study were 15 students of Group A of TK Kindergarten in Temanggung Regency. Data collection methods used are observation, interviews, and documentation. The conclusion of this study is that playing building blocks has proven to be effective in increasing the creativity of children in Group A of Temanggung District Kindergarten 2016/2017 Academic Year. This is indicated by the achievement of completeness criteria in the classroom action research that has been carried out. Completeness of learning outcomes of children who get very good grades from Cycle I to Cycle II has increased by 60%, so that from the initial condition to Cycle II it has increased by 73.3%. In the performance indicators the researchers determined 80% of children could show their creativity, in Cycle II it had exceeded the expected target of 86.7% of children being able to show their creativity in creating a form using building blocks and telling the results of their work.